2015
DOI: 10.1002/2327-6924.12212
|View full text |Cite
|
Sign up to set email alerts
|

Sleep impairment and insomnia in sickle cell disease: A retrospective chart review of clinical and psychological indicators

Abstract: Purpose To examine clinical and psychological indicators associated with sleeplessness and insomnia in adult patients with sickle cell. Data sources PubMed, Scopus, Cochrane Library. Data were collected from adult sickle cell participants (N = 72) in outpatient clinics at a Midwest National Cancer Institute designated comprehensive cancer center. A retrospective chart review observed for clinical and psychological indicators associated with sleeplessness and insomnia. Conclusions Findings included that adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
(49 reference statements)
1
11
0
Order By: Relevance
“…Based on a manual chart review of approximately 50 random insomnia patients, details such as the frequency of symptoms per week or the duration of symptoms, which would be necessary for a DSM-V diagnosis, were not documented for the vast majority of patients. These observations from our data are consistent with a previous report 56 . As a result, criteria such as DSM-V would be impractical to classify the insomnia status of patients in the EMR.…”
Section: Methodssupporting
confidence: 94%
“…Based on a manual chart review of approximately 50 random insomnia patients, details such as the frequency of symptoms per week or the duration of symptoms, which would be necessary for a DSM-V diagnosis, were not documented for the vast majority of patients. These observations from our data are consistent with a previous report 56 . As a result, criteria such as DSM-V would be impractical to classify the insomnia status of patients in the EMR.…”
Section: Methodssupporting
confidence: 94%
“…In children, specific sleep disturbances associated with the sleep disorder insomnia, namely difficulty falling asleep and staying asleep, have been identified using daily sleep diaries (Valrie, Gil, Redding-Lallinger, & Daeschner, 2007a). In addition, using retrospective chart review, one recent study found insomnia symptoms were documented for 47% of the adults with SCD in that study (Mann-Jiles, Thompson, & Lester, 2015). Qualitative literature on sleep disturbances suggests that sleep disturbances have been reported as a distressing symptom (Panepinto, Torres, & Varni, 2012; Weisberg, Balf-Soran, Becker, Brown, & Sledge, 2013) and a quality of life priority for individuals with SCD (Treadwell, Hassell, Levine, & Keller, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[42] However, various factors can contribute to sleep disturbances, including stress from home and school. [43] Research has shown that sleep problems are associated with increased physical, mental, and environmental health issues. [43] In the case of individuals with SCA, episodes of acute pain known as VOC and sleep-disordered breathing have been identified as significant contributors to poor sleep.…”
Section: Discussionmentioning
confidence: 99%